Lightweight and resilient SiOC/SiC foam with efficient electromagnetic wave absorption and high‐temperature stability. Issue 5 (6th January 2023) - Niu, Min; Wang, Hongjie; Su, Lei; Cai, Zhixin; Lu, De; Gao, Hongfei; Xu, Liang; Peng, Kang; Zhuang, Lei; Fu, Wei
Abstract: Integrating multiple functions such as high electromagnetic (EM) wave absorption, thermal insulation, and resilience into one material is critical, especially for applications in harsh environment. SiC ceramic has received considerable attention as high‐temperature wave absorber, but its applications are limited by common wave absorption performance and brittleness of ceramics. Here by incorporating SiO2 with SiC in a unique three‐dimensional network structure, SiOC/SiC foam consisting of abundant SiOC thin flakes interconnected by numerous long interweaving SiC nanowires have been prepared. The foam shows high EM wave absorption with minimum reflection loss of −30.23 dB, broad effective absorption bandwidth of 5.4 GHz, and a nearly complete compressive resilience from 10% strain. Besides, the foam displays high‐temperature resistance up to 1400°C in air and good thermal insulation performance. Such multifunctional material is promising for applications in advanced aerospace industry under extreme conditions.